Strategi Penetrasi Pasar Global: Eksplorasi Bibliometrik tentang Pemasaran Internasional, Mode Masuk Pasar, dan Strategi Ekspor - Yuniarti Utami , Eva; Manshur Al Ahmad, Ana Shohibul; Pratama, Rohmawan Adi; Yuninata, Dama; Prihandoko, Lastika Ary (Universitas Nusa Putra, 2023)
The global business landscape is characterized by rapid change and increasing complexity. In this dynamic environment, understanding firms' strategies to penetrate international markets is crucial. This study conducts a comprehensive bibliometric analysis to uncover the intellectual landscape of global market penetration strategies in international marketing, market-entry, and export strategies. Through careful examination of influential authors, essential works, research clusters, and emerging trends, this study offers valuable insights into the state of the field. Leading authors such as Ravi Ramamurti, Mike W. Peng, and Jean-François Hennart have significantly shaped our understanding of emerging market multinationals and internationalization strategies. Their seminal works have challenged conventional paradigms and encouraged innovative thinking. Identifying research clusters underscores the multifaceted nature of global market penetration, covering market entry modes, internationalization theory, and emerging market dynamics. Emerging digitalization, e-commerce, and sustainability trends highlight the ever-evolving international marketing landscape. The implications of this analysis extend to researchers, educators, policymakers, and practitioners, providing valuable guidance for future research, curriculum development, policy formulation, and strategic decision-making in the global arena.